Uma arquitetura para autoria ubíqua de documentos a partir de apresentações de TV Digital - Melo, Erick Lazaro (2010)
People comment about TV programs while watching. The technology found at Digital TV environment allow capturing and storing those comments. The combination between comments and the original program can result in a new multimedia document with personalized content. This is an ubiquitous authoring (editing) approach. This work explore the capture and access concepts and propose an architecture to allow the ubiquitous authoring of multimedia documents by end-user while a base-document is presented. The result of this activity is a new multimedia document which can replace the original document on-the-fly, changing the user experience. The main modules of the architecture are: client editing manger, code generator, private base manager, state machine manager, enhanced input manager, framebuffer recorder, elementary stream recorder, formatter (presentation engine) and media players. The proposed architecture was integrated to the Brazilian Digital TV Middleware (Ginga). The NCL language features like live editing, support to multi devices and documents seems interesting to apply the proposed model. Ginga supports NCL language and has open specifications and a reference implementation that can be reused. The reference implementation was expanded by adding new components and reusing others.